Development of Finance Students’ Professional Culture in Ukrainian Colleges - Petrenko, Larysa; Pilevich, Oksana; Zelikovska, Olena; Doronina, Natalia; Kupriyevych, Viktoriya; Bilanych, Halyna; Solovey, Nina; Isaieva, Svitlana; Selezen, Hanna (Journal of Education Culture and Society, 2022)
Aim. The purpose of the research is to develop and substantiate a theoretical model for the formation of a professional culture of finance students. Methods. The authors used a set of interrelated methods: comparative analysis, comparison and synthesis, appropriate for modelling professional culture as a pedagogical phenomenon, and functional-structural analysis for systematisation of the stages of building the professional culture. A theoretical model of professional culture has been designed and validated. This model consolidates research from studies of motivation, cognitive sciences, organisational behaviour, and values in educational and financial institutions and lays the foundations of finance students’ professional culture formation methodology. Results. The obtained results showed positive dynamics in the formation components (motivational, creative, organisational and axiological) of the theoretical model of professional culture development. Our findings confirmed that the cultural and educational environment encourages students’ engagement in learning, boosts the development of their motivational and semantic sphere, ensuring the implementation of individual learning trajectories. Conclusion. The complex of methods implemented evidences the educational, cultural, and innovative potential of the college for training and students’ personal and professional development. The structure of the professional culture development model for finance students has driven a reconsideration of the content of their professional training, generation and dissemination of novel methods and technologies. Practical implementation. The research has resulted in changes to the vocational training programmes for college finance students, the introduction of teaching methods for professional disciplines that proved their efficiency, and development of cooperation with banking institutions, financial and insurance companies.